Prediction of Past SARS-CoV-2 Infections: A Prospective Cohort Study Among Swiss Schoolchildren - Blankenberger, Jacob; Haile, Sarah R.; Puhan, Milo A.; Berger, Christoph; Radtke, Thomas; Kriemler, Susi; Ulyte, Agne (Frontiers in Pediatrics, 2021)
Objective: To assess the predictive value of symptoms, sociodemographic characteristics, and SARS-CoV-2 exposure in household, school, and community setting for SARS-CoV-2 seropositivity in Swiss school children at two time points in 2020. Design: Serological testing of children in primary and secondary schools (aged 6-13 and 12-16 years, respectively) took place in June-July (T1) and October-November (T2) 2020, as part of the longitudinal, school-based study Ciao Corona in the canton of Zurich, Switzerland. Information on sociodemographic characteristics and clinical history was collected with questionnaires to parents, information on school-level SARS-CoV-2 infections with questionnaires to school principals. Community-level cumulative incidence was obtained from official statistics. We used logistic regression to identify individual predictors of seropositivity and assessed the predictive performance of a symptom- and exposure-based prediction model. Results: 2496 children (74 seropositive) at T1 and 2152 children (109 seropositive) at T2 were included. Except for anosmia (odds ratio 15.4, 95% confidence interval [3.4–70.7]) and headache (2.0 [1.03–3.9]) at T2, none of the individual symptoms were significantly predictive of seropositivity at either time point. Of all the exposure variables, a reported SARS-CoV-2 case in the household was the strongest predictor for seropositivity at T1 (12.4 [5.8–26.7]) and T2 (10.8 [4.5–25.8]). At both timepoints, area under the receiver operating characteristic curve was greater for exposure-based (T1: 0.69, T2: 0.64) than symptom-based prediction models (T1: 0.59, T2: 0.57). Conclusions: In children retrospective identification of past SARS-CoV-2 infections based on symptoms is imprecise. SARS-CoV-2 seropositivity is better predicted by factors of SARS-CoV-2 exposure, especially reported SARS-CoV-2 cases in the household. Predicting SARS-CoV-2 seropositivity in children in general is challenging, as few reliable predictors could be identified. For an accurate retrospective identification of SARS-CoV-2 infections in children serological tests are likely indispensable.